Genetic variability and character association in lemongrass (Cymbopogon flexuosus L. Stapf) - Tiwari, S P Singh, H P Singh, A K Singh, R K (Journal of Spices and Aromatic Crops, 2005)
The variability and association of genetic parameters of nine genotypes of lemongrass (Cymbopogon flexuosus) was studied at Lucknow (Uttar Pradesh). The genetic differences were highly significant for oil, citral, geraniol and geranyl acetate contents and herb and oil yield. High heritability estimates in broad sense were observed for all the characters. High heritability with low genetic advance recorded for oil and geranyl acetate contents indicated that these characters are under non-additive gene action. Oil yield was positively and significantly associated with herb yield and oil content. Maximum direct effect of herb yield on oil content and oil yield was also observed.